Patrimonialismo e Políticas Públicas de Desenvolvimento Agrícola do Município de Bragança no Estado do Pará - Vieira, Fernando Augusto Prudente (2021)
The present article approaches the patrimonialistas characteristics gifts in the Brazilian society and its direct consequences for efetivação of public politics. In the specific case we make one brief analysis of the patrimonialista legacy and theimperramento of public politics, aiming at the agricultural development in the City of Bragança, in the State of Pará. With the purpose to perceive if this patrimonialista legacy it is present in the current days in the local politics of theCity of Bragança we leave of the analysis of the Organic Law of the revised City of in 12 of October of 1998 and its alterations.